Design Capacity Tables for Structural Steel Based on SNI 03-1729-2002: Built-up Sections. (2015) - Tanojo, Effendy; Pudjisuryadi, Pamuda; Candra, Billy Prawira; William, Welly
Abstract: Structural steel is commonly used as construction material. In designing structural steel, practitioners typically use the steel section properties table to obtain the necessary data needed to calculate the nominal strength of the selected section. The commercially available section properties tables in Indonesia typically list the weight, section area, inertia, radius of gyration, and section modulus of the commercially available steel sections. In many cases, it is not uncommon for built-up sections to be used as structural members. The section properties of these built-up sections are not readily available in the aforementioned section properties table. A series of tables have been developed to enlist the section properties of the built-up sections that are commonly used in Indonesia. Moreover, these tables also provide the nominal strength of the built-up sections with respect to several loads, i.e. tension, compression, bending, and shear. These nominal capacities will enable the practitioners to design built-up structural steel sections more easily and efficiently.